Three-dimensional VLC indoor positioning system using smart device camera receiver with image processing technique - P. Rattakorn (2020)
© 2020 SPIE. In this paper, we propose a three-dimensional VLC indoor positioning system using smart device camera receiver whereby the rolling shutter effect of CMOS camera sensor to detect the encoded identification data and necessary information regarding transmitter positions from the individual LEDs. No prior assumptions have been made regarding each LED transmit power, this allows for non-identical LEDs and their power deterioration over time. Images of 4 LEDs are required to estimate the receiver position. In the image capturing process, it is necessary to adjust the exposure setting. The captured images are processed by converting them to black and white where the black and white stripes may be decoded. Then by applying a different threshold, we propose a method to use the white pixel area (counted in number of pixels), corresponding to each LED image, to estimate the distance between each LED and the receiver. These estimations are used in trilateration algorithm to determine the receiver position. Through proper calibration, the position error is within 10 cm.